An exploratory study of residential child abduction: An examination of offender, victim and offense characteristics. (September 2016) - Shelton, J.; Hilts, M.; MacKizer, M.
Abstract: Child abduction is every parent and community's worst nightmare. Specifically, a child abducted from inside a residence can be a source of great panic and give the perception that the four walls of one's home offer little or no protection from offenders who kidnap children. This emotionally charged crime can quickly overwhelm law enforcement agencies, particularly those with limited resources. The study, conducted by the FBI's Behavioral Analysis Unit III-Crimes Against Children, analyzed the characteristics of 32 cases in which a child was abducted from inside a residence. The findings are particularly salient to law enforcement officers who are confronted with a report of a child missing from a residence and initially must consider the possibility that an intruder kidnapped the child. The research was conducted for the purpose of identifying common characteristics of this unique type of child abduction in order to assist law enforcement agencies in narrowing the focus and scope of their investigation. Highlights: 32 cases in which a child was abducted from inside their residence were reviewed Most residences were unlocked and offenders entered during the overnight/ early morning hours Over half of the offenders were known to the victim or the victim's family Burglary was the most common crime in the offenders' criminal arrest histories The victim's sibling often detected or witnessed the offender during the abduction but delayed notifying adults in the residence